2020
DOI: 10.3390/agronomy10121998
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-by-Environment Interaction Effects under Heat Stress in Tropical Maize

Abstract: Spring maize area has emerged as a niche market in South Asia. Production of maize during this post-rainy season is often challenged due to heat stress. Therefore, incorporating heat stress resilience is an important trait for incorporation in maize hybrids selected for deployment in this season. However, due to the significant genotype × environment interaction (GEI) effects under heat stress, the major challenge lies in identifying maize genotypes with improved stable performance across locations and years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…In the current study, we used GWAS approach to identify SNP markers associated with cold stress tolerance in a panel of tropical maize lines screened under field conditions. The current panel of lines had a high LD decay which is typical of tropical germplasm 63 65 , which indicates the diversity among the lines involved and the amenability to high resolution mapping studies.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In the current study, we used GWAS approach to identify SNP markers associated with cold stress tolerance in a panel of tropical maize lines screened under field conditions. The current panel of lines had a high LD decay which is typical of tropical germplasm 63 65 , which indicates the diversity among the lines involved and the amenability to high resolution mapping studies.…”
Section: Discussionmentioning
confidence: 72%
“…The current panel of lines had a high LD decay which is typical of tropical germplasm [63][64][65] , which indicates the diversity among the lines involved and the amenability to high resolution mapping studies. The current study identified a suite of significant SNPs for various traits recorded under cold stress at different crop stages across various locations.…”
Section: Discussionmentioning
confidence: 73%
“…Zaidi). In general, spring maize segment in South Asia comprises >37 • C temperature leads to heat-stress (Thayil et al, 2020). Day maximum-minimum temperature data was collected for January 2020-April 2021 from the Directorate of Agricultural Research, Khajura, Banke (Nepalgunj) district at the time of the survey, and given in Figure 2.…”
Section: Climatic Condition Of Study Locationmentioning
confidence: 99%
“…In maize, the favorable soil temperature for seedling growth is 26 • C, and when this temperature rises, root and shoot mass both decline by 10% for each degree of increase until 35 • C when growth is severely retarded (Walker, 1969). The most critical stages for heat stress are from tassel emergence to early grain filling (Nejad et al, 2017;Thayil et al, 2020). At elevated temperatures, the number of fertilized ovules that develop into grain decreases (Schoper et al, 1987a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Improving heat tolerance in maize has become one of the top priorities for maize-breeding programs. In maize, a large variation in heat tolerance exists in germplasm collections due to its successful acclimation from the tropics to temperate regions in the Northern and Southern Hemispheres [ 87 , 88 , 89 , 90 , 91 , 92 ]. The development of heat-tolerant maize hybrids is urgently needed, and this goal largely depends on the study of physiological, biochemical, and molecular mechanisms.…”
Section: Conclusion Prospects and Maize Breedingmentioning
confidence: 99%